Formulas and functions, Microsoft Excel 2010 - McFedries, Paul (MrExcel library., 2011)
MASTER CORE EXCEL 2010 TOOLS FOR BUILDING POWERFUL, RELIABLE SPREADSHEETS! Excel expert Paul McFedries shows how to use Excel 2010's core features to solve problems and get the answers you need! Using real-world examples, McFedries helps you get the absolute most out of breakthrough Excel 2010 improvements-from Sparklines to the brand-new version of Solver. Along the way, you'll discover the fastest, best ways to handle essential day-to-day tasks ranging from generating account numbers to projecting the impact of inflation.Becoming an Excel expert has never been easier! You'll find crystal-clear instructions... insider insights... even complete step-by-step projects for building timesheets, projecting cash flow, aging receivables, analyzing defects, and more. • Create more powerful formulas • Use conditional formatting to instantly reveal anomalies, problems, or opportunities • Analyze your data with standard tables and PivotTables • Use complex criteria to filter data in lists • Understand correlations between data • Perform sophisticated what-if analyses • Use regression to track trends and make forecasts • Build loan, investment, and discount formulas • Troubleshoot problems with formulas, ranges, and functions About MrExcel Library: Every book in the MrExcel Library pinpoints a specific set of crucial Excelskills, and presents focused tasks and examples for performing them rapidly and effectively. Selectedby Bill Jelen, Microsoft Excel MVP and mastermind behind the leading Excel solutions website MrExcel.com, these books will: • Dramatically increase your productivity-saving you 50 hours a year, or more • Present proven, creative strategies for solving real-world problems • Show you how to get great results, no matter how much data you have • Help you avoid critical mistakes that even experienced users make Paul McFedries, president of Logophilia Limited, is a Microsoft Office expert and full-time technical writer. Paul has been authoring computer books since 1991 and has more than 70 books to his credit, which combined have sold more than three million copies worldwide. His recent titles include Using the Microsoft Office Web Apps, and Microsoft Windows 7 Unleashed. He is also proprietor of Word Spy (www.wordspy.com), a website that tracks new words and phrases as they enter the English language.